Influence of process variables on spray agglomeration process in a continuously operated horizontal fluidized bed - Du, J.; Bück, Andreas; Tsotsas, E. (Powder Technology, 2020)
Experiments on continuously operated spray fluidized bed agglomeration are presented in this work. The process is conducted with glass beads and water-based binder hydroxypropylmethylcellulose (HPMC). By varying the process parameters, the results show that by the decrease of air temperature or feed rate and by the increase of binder concentration, larger particles can be achieved. Larger particle size also results in higher bed mass and more fluctuations in the process. Besides parameters variations, different internal and outlet weir configurations are used. Tracers are used in the experiments to characterize the particle residence time distribution. The separation effect can be decreased and the particle residence time can be optimized by the installation of internal weirs and lower height of outlet weir. The results show that the jets from the spray nozzles are increasing the motion and mixing of particles significantly.
CRIS-Team Scopus Importer:2020-01-24
Keywords: Continuous process; Horizontal fluidized bed; Residence time distribution; Spray agglomeration